(untitled) (Research, Society and Development, 2021)
Objective: this study aims to report and analyze how mothers experience, from the diagnosis of microcephaly, of the child, as a result of Zika Virus infection. Materials and methods: this research is a descriptive study, with a qualitative approach, carried out with two mothers of children with microcephaly, living in a municipality located in the Midwest region, in Mato Grosso, in Brazil. The accounts were carried out in 2018 and analyzed through content analysis, in the thematic modality. Results: as mothers, who experience the experience of having a child with microcephaly, they reacted to the diagnosis with surprise and despair and to grief with anguish and pain. In addition, as parents of little knowledge about the disease and prognosis. This investigation evidences the change in the family dynamics, facing the disease, and the difficulties in the interaction of the family with the basic health sector. Conclusion: the records indicate that there is an urgent need for permanent and comprehensive care for mothers, so that health care is extended, not only to children, but also to the family unit.